Cardiac Surgery 2019 Reviewed - Doenst, Torsten; Bargenda, Steffen; Kirov, Hristo; Moschovas, Alexandros; Tkebuchava, Sophie; Safarov, Rauf; Velichkov, Ilia; Diab, Mahmoud (The Thoracic and Cardiovascular Surgeon, 2020)
For the year 2019, almost 25,000 published references can be found in PubMed when entering the search term “cardiac surgery.” We used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses approach for article selection and reviewed the main fields of adult cardiac surgery (i.e., coronary, valve, aortic, and heart failure surgery). The past decade has experienced an enormous development of interventional techniques that compete more and more with classic surgery. This contest was broadly visible in 2019. It peaked over the interpretation of the EXCEL trial data, where percutaneous coronary intervention and coronary artery bypass grafting (CABG) for left main disease were compared. A novel pathomechanism for CABG was proposed, potentially answering open questions in the field. In aortic valve surgery, two low-risk trials comparing transcatheter aortic valve implantation (TAVI) to classic aortic valve replacement (surgical aortic valve replacement) received attention for showing equal or superior short-term outcomes for TAVI. Longer follow-up information from recent trials became available presenting results emphasizing the need for joint decision making. While publications addressing surgery on the aorta and the mitral and tricuspid valves were less abundant, there was substantial activity regarding left ventricular assist device support and heart transplantation. This article attempts to summarize the most pertinent publications. It does not expect to be complete and cannot be free of individual interpretation. We aimed to provide a condensed summary of 2019s publications with a stimulus for in-depth reading and a basis supporting patient information.
Keywords: coronary revascularization; aortic valve surgery; mitral valve surgery; tricuspid valve surgery; left ventricular assist device; heart transplantation